Innovative approaches to tuberculosis diagnosis with emphasis on nucleic acid amplification tests in a resource constrained high burden tuberculosis setting - Fourie, Petrus Bernardus (University of Pretoria, 2015)
Thesis (PhD)--University of Pretoria, 2015.